2009
DOI: 10.1021/tx900096j
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Synthesis of Two Series of Nerve Agent Model Compounds and Their Stereoselective Interaction with Human Acetylcholinesterase and Human Butyrylcholinesterase

Abstract: Both G-and V-type nerve agents possess a center of chirality about phosphorus. The S p -enantiomers are generally more potent inhibitors than their R p -counterparts toward acetylcholinesterase (AChE) and butyrylcholinesterase (BChE). To develop model compounds with defined centers of chirality that mimic the target nerve agent structures, we synthesized both the S p and R p stereoisomers of two series of G-type nerve agent model compounds in enantiomerically enriched form. The two series of model compounds co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(70 citation statements)
references
References 39 publications
3
67
0
Order By: Relevance
“…13. Time course for inhibition of rat plasma cholinesterase functional activity by nerve agent model compound Sp-GD tertiary amine (Barakat et al, 2009) or GD after administration to rats. (A) Comparison of inhibition of rat plasma cholinesterase by nerve agent model compound Sp-GD (u) (250 mg/kg, i.p.)…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…13. Time course for inhibition of rat plasma cholinesterase functional activity by nerve agent model compound Sp-GD tertiary amine (Barakat et al, 2009) or GD after administration to rats. (A) Comparison of inhibition of rat plasma cholinesterase by nerve agent model compound Sp-GD (u) (250 mg/kg, i.p.)…”
Section: Discussionmentioning
confidence: 99%
“…(B) Comparison of time course (0-10 days) for inhibition of rat plasma cholinesterase activity by nerve agent model compound Sp-GD tertiary amine (u) (250 mg/kg, i.p.) (Barakat et al, 2009) and GD (◯) (25.5 mg/kg, i.p.) (modified from Jovic, 1974).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this article, we describe the development and validation of a novel screening method that identified hBChE variants with a decreased rate of inhibition by OPs. Because the use of chemical warfare agents is strictly regulated, we used nerve-agent model compounds that have been shown to have similar functional properties to authentic OP compounds (Barakat et al, 2009;Gilley et al, 2009). OP model compounds not only served as a useful means for screening hBChE variants in molecular evolution screening, but also were used in kinetic studies of variants identified (Ralph et al, 2011).…”
Section: Introductionmentioning
confidence: 99%